Exploring the role of brain-derived extracellular vesicles in viral infections: from pathological insights to biomarker potential - Oberholster, Larise; Du Pasquier, Renaud; Mathias, Amandine (Frontiers in Cellular and Infection Microbiology, 2024)
Extracellular vesicles (EVs) are membrane-bound vesicles secreted by all cell types that play a central role in cell-to-cell communication. Since these vesicles serve as vehicles of cellular content (nucleic acids, proteins and lipids) with the potential to cross biological barriers, they represent a novel attractive window into an otherwise inaccessible organ, such as the brain. The composition of EVs is cell-type specific and mirrors the physiological condition of the cell-of-origin. Consequently, during viral infection, EVs undergo significant changes in their content and morphology, thereby reflecting alterations in the cellular state. Here, we briefly summarize the potential of brain-derived EVs as a lens into viral infection in the central nervous system, thereby: 1) uncovering underlying pathophysiological processes at play and 2) serving as liquid biopsies of the brain, representing a noninvasive source of biomarkers for monitoring disease activity. Although translating the potential of EVs from research to diagnosis poses complexities, Characterizing brain-derived EVs in the context of viral infections holds promise to enhance diagnostic and therapeutic strategies, offering new avenues for managing infectious neurological diseases.